Efeitos do Programa de Aquisição de Alimentos – PAA, no estado de Alagoas na perspectiva do desenvolvimento territorial rural - Moura, Antonio Marcos Pontes de (2021)
Family farmer is a part of social category that plays an important role in food production, however, he/she faces difficulties regarding the flow of his production and access to markets. Therefore, the creation of The Food Purchase Programme – PAA (in its Portuguese abbreviation) becomes essential for the inclusion of family farming, while promoting food and nutritional security in the context of rural development in the territory. The object of study of this thesis seeks to point out the PAA as a program to combat hunger and strengthen family farming whereas access to markets and guaranteeing income, achievement in the countryside and autonomy. In view of this, Purchase for Simultaneous Donations – CDS (in its Portuguese abbreviation) enables the distribution of food to the most needy represented in receiving entities of social assistance networks, causing a considered social and territorial impact, helping to reduce hunger and poverty in Alagoas like the Agreste Territory of Alagoas its main purpose was to analyze the PAA in terms of rural territorial development and its effects on the state of Alagoas. As a practical matter, two municipalities in the Territory of Agreste area of Alagoas (Palmeira dos Indios and Arapiraca) were selected and an attempt was made to understand the actions of the PAA regarding their territorial and social scope. The research is empiricalanalytical character appraising quali-quantitative data that were collected in public bodies, bibliographic survey in response to the theme of territorial policies and the PAA itself, besides to analysis categories such as family farmer, State, food security, among others. Questionnaires and selective interviews were conducted with representatives of participating cooperatives, suppliers, producers, receiving units, representatives of public bodies or entities, and photographic records and mappings can still be carried out. The specific field work. The specific field work took place in the Food Supply and Distribution Centers in the municipalities of Arapiraca and Palmeira dos Indios and in the receiving unit - Capiata e Povoado Amaro Community Association in the respective municipalities. This information provided a qualitative analysis of the research and gave the conditions to assess the PAA in the Alagoas’ state, the data collected in the field demonstrate that the PAA is not a determining factor for rural territorial development, but contributes to this process, especially when the rural policies that the Territories of Citizenship were able to add were added. Currently, the PAA is led by the actions of states and municipalities that are even more dependent on federal resources in search of overcoming and maintaining the program in contradiction to the cuts in resources that generated a crisis in the program. The institutional reinforced resistance comes from the importance of maintaining the PAA due to its social importance in the combat against hunger and poverty.